Power and Society in Russia during the First World War: The Rewiev of Modern Russian Historiography - Nailevich Valiakhmetov, Albert (2021)
Relevance of the investigated topic is determined by the fact that modern historiography considers the society not only as a receptor but also as independent actor with its own purposes, ideas and interests.  The study of society, which is under emergency conditions (wars, revolutions, etc.), is especially interesting for historians and other social sciences researchers. The investigation of historical experience of power and society interaction in Russia can be interesting under modern Russian conditions. The object of the given article is modern Russian historiography of World War I. The article aims to characterize the modern Russian historical literature, which deals with the power and society interaction in Russia in 1914-1917 (from the beginning of World War until the February Revolution in Russia). The authors describe the impact not only internal (source study, methodology) but also external (social and political aspect) factors on historiography. They made a conclusion that modern Russian historians consider the power and society interaction from two main points of view (social and political spheres), describe it as generally constructive and emphasize that at one point collaboration was replaced by confrontation (especially in the political sphere).   In modern Russian historiography, there are controversial opinions about some problems (for example, who initiated the interaction: power or society). The materials of the article can be helpful for historians, university professors, teachers, who deal with problems of history of Russian historical science and Russian history of early XX century.